2017
DOI: 10.15835/nbha45110651
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Morphological Changes and Storage Root Yield of Sweetpotato [Ipomoea batatas (L.) Lam.] under PEG-Induced Water Stress

Abstract: Sweetpotato is an important tuberous root crop rich in nutrients such as vitamins and carbohydrates, and can grow well in arid regions with less water consuming crop. The aim of this research was to evaluate the storage root yields, physiological, biochemical and morphological traits in sweetpotato cv. 'Japanese Yellow' subjected to polyethylene glycol (PEG)-induced water deficit. At harvest (4 months after planting) the number of storage roots per plant and storage root fresh weight in sweetpotato treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…As shown in Fig. 4, the increasing trends of soluble sugar and proline contents observed in both herbaceous peony cultivars under drought stress mirror previous findings of some tuberous root plants such as Dahlia pinnata (Fan et al, 2011), Ipomoea batatas (Yooyongwech et al, 2017), and P. suffruticosa 'Luo Yang Hong' and 'Hu Hong' (Kong et al, 2011), the latter using potted plants with four levels of SMC (100%, 75% as CK, 50%, and 25%). However, the variation in soluble protein content of this study was not unanimous.…”
Section: Resultssupporting
confidence: 85%
“…As shown in Fig. 4, the increasing trends of soluble sugar and proline contents observed in both herbaceous peony cultivars under drought stress mirror previous findings of some tuberous root plants such as Dahlia pinnata (Fan et al, 2011), Ipomoea batatas (Yooyongwech et al, 2017), and P. suffruticosa 'Luo Yang Hong' and 'Hu Hong' (Kong et al, 2011), the latter using potted plants with four levels of SMC (100%, 75% as CK, 50%, and 25%). However, the variation in soluble protein content of this study was not unanimous.…”
Section: Resultssupporting
confidence: 85%
“…This may be associated with root system length (Borawska-Jarmułowicz et al, 2014). A longer root system can be advantageous in the case of drought stress in the deeper soil layers, as confirmed by the study Yooyongwech et al (2017).…”
Section: Discussionsupporting
confidence: 60%
“…Results of Kingori et al (2016) suggest that nitrogen fertilization influences the physiological status of the I. batatas plants, including leaf expansion ability, stomatal conductance and chlorophyll content. A study by Brestic and Zivcak (2013) and Yooyongwech et al (2017) has revealed that photosynthesis is a metabolic process that is particularly sensitive to many stress factors. A frequent component of the so-called multistress is fertilizer stress which occurs when photosynthetic pigments absorb too much photosynthetically active radiation (PAR) energy in relation to the capacity to convert it into chemical energy during photosynthesis (Brestic, Zivcak, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations